REFORMULATION OF REGULATIONS ON INDONESIAN CITIZENS WHO HAD JOINED THE ISLAMIC STATE OF IRAQ AND SYRIA (ISIS) - Susmayanti, Riana; Nur Widhiyanti, Hanif; Efendi, Muhammad Fadli (Arena Hukum, 2023)
The repatriation of ex-ISIS members to Indonesia will have an impact on the community, because previous jihadi alumni from Afghanistan carried out terrorist bombings in several locations after they returned to Indonesia. This research will analyze the classification of Indonesian citizens who had joined ISIS; the Indonesian citizens who had joined ISIS according to Indonesian regulations and the reformulation of regulations on Indonesian citizens who had joined ISIS. This normative juridical research uses statutory approach and conceptual approach. The results of this study shows that the classification of Indonesian citizens who had joined ISIS based on hierarchy in the organization and concerned involvement in ISIS, the regulatory violations committed by Indonesian citizens by joining ISIS, and the urgency of changing the citizenship law that applies to Indonesian citizens who join ISIS.